The Influence of Media on Lifestyle, Culture, and Behaviours of Youth - Mgr. Doaré Jana (Reviews of Modern Science, 2024)
This article explores the pressing need to revitalize disappearing genres of journalism, particularly local reporting and cultural magazines, and their relevance to younger generations. As traditional media faces challenges from the digital landscape, local reporting serves as a vital connection between communities and the issues that affect them, while cultural magazines provide a platform for emerging voices and creative expression. By examining the unique contributions of these genres to society and the challenge of engaging young audiences, the article advocates for innovative strategies that leverage digital platforms, authenticity, and community ties to attract and empower the next generation of consumers and creators. Through active participation and collaboration with local organizations and educational institutions, we can cultivate a more informed, engaged, and culturally aware youth, ultimately enriching the media ecosystem and ensuring the survival and vibrancy of local journalism and cultural discourse.